Makna Leksikal dan Gramtikal dari Judul Berita Politik Media Online RiauPos.co - Sandi Irawan; Aprillia Maharani Putri; Ira Arini; Pitri Susanti; Muhammad Mukhlis (UIR Press, 2022)
Online newspapers are internet-based newspapers that contain news, articles, and features. The existence of this online news letter is no stranger to the public. This is because online newspapers also play a crucial role in everyday life and become a medium of information. Many people today misunderstand in interpreting the headlines they read. At the same time creating various perspectives in understanding news headlines (headlines). This is often due to ignorance and other factors, including misuse by the author or poor word choice, creating ambiguity among news readers. This study focuses on the lexical and grammatical meaning of political news headlines in the RiauPos.co Online media. This research was conducted in addition to providing an explanation of how news headlines (headlines) can lead to errors, but also trying to convey insights about public perceptions when reading news headlines (headlines). The research entitled